Why are Countries' Asset Portfolios Exposed to Nominal Exchange Rates? - Adams, Jonathan (IMF Working Papers; Working Paper ;, 2017)
Most countries hold large gross asset positions, lending in domestic currency and borrowing in foreign. Thus, their balance sheets are exposed to nominal exchange rates. We argue that when asset markets are incomplete, nominal exchange rate exposure allows countries to partially insure against shocks that move real exchange rates. We demonstrate that asset market incompleteness can simultaneously generate realistic gross asset positions and resolve the Backus-Smith puzzle: that relative consumptions and real exchange rates correlate negatively. We also show that local perturbation methods that use stabilizing endogenous discount factors are inaccurate when average and steady state interest rates differ. To address this, we develop a novel global solution method to accurately solve the model.